Biodegradation of Palm-based 9,10-Dihydroxystearic Acid (DHSA) in aquatic environments - Razmah, G.; Siti Afida, I.; Noorazah, Z.; Hazimah, A.H. (Universiti Kebangsaan Malaysia, 2015)
Palm-based DHSA is a new chemical developed in MPOB that has three reactive sites that would enable the preparation of many useful derivatives. New chemicals introduced into the market have to be registered and information on their environmental performance such as biodegradability has to be supplied as required under various national and international laws. Biodegradability screening tests, such as the OECD 301 series, are basic tools for assessment of the environmental fate of chemicals in aquatic environments. A substance is considered readily biodegradable when its biodegradability reaches the pass levels of 60% carbon dioxide (CO2)/theoretical carbon dioxide (ThCO2) evolution, 60% biochemical oxygen demand (BOD)/theoretical oxygen demand (ThOD) or 70% dissolved organic carbon (DOC) removal within 28 days. Palm-based DHSA was found to be readily biodegradable where its biodegradability reached 65% within 28 days test period determined via the OECD 301C Modified MITI (I) test method, which passed the 60% level of BOD/ThOD requirement as stipulated in the OECD Guidelines for testing of chemicals. This result is indicative of DHSA’s rapid degradation in aquatic environments. Hence, DHSA is not expected to accumulate in the food chains and will not pose problems in the aquatic environments although it is poorly soluble in water.